In Patagonia (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
There is a sentence that has stirred the imagination of Europe as powerfully as any call to arms. I’ve seen it written a hundred times, and have always felt a pang of envy for its lucky author. It is so jaunty, so unreasonably larger than life. It promises to deliver the unexpected –some fantastic reversal of fortune, some miraculous transformation in the character of the writer. It deserves a paragraph to itself, and should be printed in ceremonious italics.